2019
DOI: 10.1038/s41598-018-38276-x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Roles of Discharge, Slope and SOC in DOC Transport in Small Mountainous Rivers, Taiwan

Abstract: Riverine dissolved organic carbon (DOC), responsible for riverine productivity, is rarely documented in subtropical small mountainous rivers (SMRs) where high rainfall and steep slopes are the main features. This study investigated the DOC export at eight sites in three Taiwan SMRs to characterize the dynamics and controlling factors of DOC transport. Results showed that the mean DOC concentration of ~0.78 mg L−1 is much lower than the global average of ~5.29 mg L−1. However, the mean DOC yield, ~22.51 kg-C ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…Our results showed that DOC concentration and river discharge had a significant positive correlation ( n = 12; p < 0.01) in the lower Changjiang River (Figure 5a), indicating a general hydrological control on DOC abundance. Similar positive correlations between DOC and discharge have been observed in other rivers, such as the arctic rivers (Guo et al., 2012; Raymond et al., 2007), the Mississippi River (Cai et al., 2015), and some small rivers (Lee et al., 2019; Warnken & Santschi, 2004). In summer, the flooding would have flushed more organic‐rich soils from deep flow paths, likely through soil erosion and DOM leaching in the river.…”
Section: Discussionsupporting
confidence: 67%
“…Our results showed that DOC concentration and river discharge had a significant positive correlation ( n = 12; p < 0.01) in the lower Changjiang River (Figure 5a), indicating a general hydrological control on DOC abundance. Similar positive correlations between DOC and discharge have been observed in other rivers, such as the arctic rivers (Guo et al., 2012; Raymond et al., 2007), the Mississippi River (Cai et al., 2015), and some small rivers (Lee et al., 2019; Warnken & Santschi, 2004). In summer, the flooding would have flushed more organic‐rich soils from deep flow paths, likely through soil erosion and DOM leaching in the river.…”
Section: Discussionsupporting
confidence: 67%
“…Riverine DOC (i.e., baseflow and storm events) is rarely documented in small headwater catchments across the tropics, whereby heavy rainfall, dynamic riparian areas, steep slopes, soil characteristics, low stream water pH, and high solar radiation exposure (Figure ) are key features controlling SOC mobilization (Lee et al, ; Shih et al, ; Wymore et al, ). This study demonstrated that large daily rainfall up to 250 mm (a typical rainfall amount during tropical storm passages; Zhang et al, ) and sustained saturation within riparian areas (Figures a and ) led to rapid allochthonous DOC transport to the stream network (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…Global DOC export usually ranges from 1 to 15 g C · m 2 · year ‐1 (Neff & Asner, ), with a mean annual value of 1.08 g C · m 2 · year ‐1 (Li et al, ; Table ). While large tropical river systems (e.g., Amazon, Mekong, Orinoco, Parana; Table ) exhibited DOC export values between ~2‐5 g C · m 2 · year ‐1 , pristine and dynamic tropical forested catchments, such as Quebrada Grande, revealed a significant potential to export greater DOC amounts, in most cases, than temperate and arctic streams or large river systems (Lee et al, ). Baseflow and storm events contributed 37.8% and 62.2%, respectively, to the total discharge‐weighted DOC export from Quebrada Grande (6.7±0.1 g C · m ‐2 · year ‐1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This also indicates that low relief regions with stronger hydrologic connectivity to streams and rivers are likely a major source of riverine DOC (Connolly et al, 2018;Mzobe et al, 2020). The shallow soil depth in steeper regions may also be an influencing factor in constraining DOC generation (Lee et al, 2019). The correlation of SUVA254 with mean drainage slope suggests that steeper catchments tend to export DOC with less aromaticity (Fig.…”
Section: Geomorphologic Controls On Doc Exportmentioning
confidence: 92%